KONSEP NASIONALISME DI BALIK SEJARAH PENULISAN PUISI 'DIPONEGORO' DAN 'TANAH AIR MATA': KAJIAN SASTRA BANDINGAN - Wijayanti Ismail; Yosi Wulandari (Faculty of Cultures and Languages UIN Raden Mas Said, 2021)
This study aimed at describing the nationalism concept behind the history of poetry writing of two poets from different exponents, namely Exponent 45 and Exponent 70. The focus of this study lied in the viewpoints of the two poets towards nationalism meanings reflected in their poems. The method applied in this study was descriptive-comparative by using comparative literature approach. The results show that in the poem Diponegoro that was written by Chairil Anwar, nationalism is seen as an effort of the country to liberate its people from colonialism. Meanwhile, in the poem Tanah Air Mata, a work of Sutardji Calzoum Bachri, nationalism is viewed as the manifestation of people’s love to their country in order to defend the independence of their nation and state.